Improving Students’ Vocabulary Mastery Using Mind Map - Fitria Wulan Sari; Madya Giri Aditama (Journal of English Language Teaching and Islamic Integration, 2020)
This article focuses on describing the use of Mind Map to increase students’ vocabulary mastery. The objective of this research was to improve students’ vocabulary mastery by applying Mind Map. It was descriptive qualitative research. The method used in this research is Classroom Action Research (CAR) which consists of Planning, Acting, Observing, and Reflecting. This research was managed in two cycles. The participants of this research were first semester students in one of the universities in North Maluku. The instruments used in this research were observation and test. From the data collection, it can be drawn a conclusion that the use of mind map was able to improve students’ vocabulary mastery. After analyzing the data sources, it was found that there was improvement score from the pre-test and post-test. The mean score of pre-test was 54, 91 and the post-test was 83, 43. Thus, it can be concluded that Mind Map is an appropriate method to improve the students’ vocabulary mastery.